Profile of functional amblyopia cases seen by optometrists in the Ministry of Health (MOH) Malaysia hospitals - Duratul Ain Hussin; Mahani Mohd Salleh; Che Ruhani Che Jaafar; Rini Roslina Amir; Farahiyah Ibrahim; Nor Aini Hanafi (penerbit ukm, 2013)
Amblyopia is one of the most common causes of visual defi cit in children. Presently, in the Ministry of Health Malaysia hospitals, there is no documented data on the characteristic and profi le of amblyopia cases. This study was conducted to describe the profi le of new amblyopia cases seen by optometrists at the Ministry of Health (MOH) Hospitals. This study was a retrospective and multicenter study including all MOH hospitals with optometry clinics. Clinical record data of amblyopic patients aged 3 to 17 years old who were newly diagnosed between 1st August 2010 to 31st January 2011 and who fulfi lled the inclusion criteria were obtained. Data collected included demography, systemic history, ocular history and optometric fi ndings and diagnosis. Thirty eight MOH hospitals participated and a total of 301 patients were diagnosed with functional amblyopia within the study period. Mean age for these amblyopic patients was 7.70 + 0.16 years old. Boys were the predominant gender (57.1%) and Malay preceded the other races with a 65.4% occurrence. Mild amblyopia was found in 51.5% of the patients, 31.6% were with moderate amblyopia and only 16.9% of patients were severe amblyopia. The underlying amblyogenic causes assessed were ametropia (61.5%), anisometropia (25.2%), strabismus (9.3%) and stimulus deprivation (4.0%). Refractive error was discovered as the most common cause of amblyopia in this study. It is crucial for optometrists to detect this type of visual impairment and undertake an early optometric intervention.